Exchange Rate Effectiveness in Five ASEAN Countries: Indonesia, Malaysia, Singapore, Thailand and the Philippines - Fauzia Bakhtiar; Anggi Somba Poddala; Miftha Farild; Wahyudi Wahyudi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Exchange rate is defined as the currency that can be exchanged per unit to another currency, or the price of one currency to another currency. The purpose of this study is to determine the effect of inflation, interest rates and investment on exchange rates in five ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand, and the Philippines. The variables used in this study are exchange rates, inflation, interest rates and investment as moderating variables. Data sources come from World Development Indicators and Investing.com. The analysis used is multiple linear analysis with the help of SPSS 22 software. The results of this study indicate that inflation and interest rates have no effect on investment. In addition, inflation, interest rates and investment have no effect on exchange rates in five ASEAN countries. Then, the effect of inflation and interest rates on exchange rates through investment also does not have a significant effect.